Associations Between Objectively Measured Physical Activity and Executive Functioning in Young Adults. Issue 2 (April 2018) - Lin, Jun; Wang, Kun; Chen, Zuosong; Fan, Xiang; Shen, Liqun; Wang, Yazhou; Yang, Yanxiang; Huang, Tao
Associations between daily physical activity (PA) and executive functioning have rarely been investigated among young adults. This study examined these associations among 162 university students (74 females and 88 males; mean age = 19.0, SD = 1.1 years). We measured PA objectively, using hip-mounted accelerometers, and assessed executive functioning in a task-switching paradigm. Anthropometrics measurements were gathered using standardized procedures. Through linear regression modeling, we found moderate-to-vigorous physical activity (β = −0.19, 95% CI = [−0.35, −0.03], p  = .02) and light physical activity (β = −0.17, 95% CI = [−0.34, −0.01], p  = .04) to be associated with smaller global reaction time switch costs. Total PA was not associated with task-switching performance, and there were no statistically significant associations between PA indicators and local switch costs. As both moderate-to-vigorous and light physical activities were associated with better executive function in young adults, there can be important cognitive benefits to remaining physically active.